Gut microbiota of endangered Australian sea lion pups is unchanged by topical ivermectin treatment for endemic hookworm infection - Fulham, Mariel; Power, Michelle; Gray, Rachael (Frontiers in Microbiology, 2022)
The gut microbiota is essential for the development and maintenance of the hosts’ immune system. Disturbances to the gut microbiota in early life stages can result in long-lasting impacts on host health. This study aimed to determine if topical ivermectin treatment for endemic hookworm (Uncinaria sanguinis) infection in endangered Australian sea lion (Neophoca cinerea) pups resulted in gut microbial changes. The gut microbiota was characterised for untreated (control) (n = 23) and treated (n = 23) Australian sea lion pups sampled during the 2019 and 2020/21 breeding seasons at Seal Bay, Kangaroo Island. Samples were collected pre- and post-treatment on up to four occasions over a four-to-five-month period. The gut microbiota of untreated (control) and treated pups in both seasons was dominated by five bacterial phyla, Fusobacteria, Firmicutes, Proteobacteria, Actinobacteria and Bacteroidetes. A significant difference in alpha diversity between treatment groups was seen in pups sampled during the 2020/21 breeding season (p = 0.008), with higher richness and diversity in treated pups. Modelling the impact of individual pup identification (ID), capture, pup weight (kg), standard length (cm), age and sex on beta diversity revealed that pup ID accounted for most of the variation (35% in 2019 and 42% in 2020/21), with pup ID, capture, and age being the only significant contributors to microbial variation (p < 0.05). There were no statistically significant differences in the composition of the microbiota between treatment groups in both the 2019 and 2020/21 breeding seasons, indicating that topical ivermectin treatment did not alter the composition of the gut microbiota. To our knowledge, this is the first study to characterise the gut microbiota of free-ranging Australian pinniped pups, compare the composition across multiple time points, and to consider the impact of parasitic treatment on overall diversity and microbial composition of the gut microbiota. Importantly, the lack of compositional changes in the gut microbiota with treatment support the utility of topical ivermectin as a safe and minimally invasive management strategy to enhance pup survival in this endangered species.